Kehidupan Mahasiswa Profesi Barista di Kota Pekanbaru - Lubis, Nopti Eliansi Br; Jalil, Ashaluddin (Journal of Education Religion Humanities and Multidiciplinary, 2024)
The city of Pekanbaru is one of the cities with a fairly rapid development of the industrial world, especially in the business industry, one of which is the very rapid development of coffee shops. The coffee shop itself is a place to gather, relax, socialize, and even to hold work meetings, with family, friends, and also colleagues. Usually, coffee shops provide several types of drinks and food, especially in the type of coffee drinks. In every coffee shop, there must be a barista as the maker or blender of the drink, but the barista's job is not only that the barista must also understand the types of coffee and the types of coffee machines. The location of this research was carried out at one of the coffee shops in Pekanbaru, namely Noa Coffee which is located on Jalan Arifin Ahmad No.70, Central Tangkerang, Marpoyan Damai District, Pekanbaru City. The purpose of the study is to find out the lifestyle of barista students in daily life and to find out the social meaning of barista for students. This research uses the Theory of Symbolic Interactionism and this research uses a qualitative method by taking 5 (five) research subjects, and using purposive techniques (intentional) or setting criteria on the subject. The data obtained in this study through primary and secondary data were collected by observation, interviews and documentation. According to the research conducted, it can be concluded that students who work as baristas mostly have the same lifestyle, but there is a slight difference in interpreting the social meaning of barista for students.